2005
DOI: 10.1039/b412419g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of fluorinated hybrid material for UV embossing of a large core optical waveguide structure

Abstract: A new organic-inorganic hybrid material (HYBRIMER) has been synthesized homogeneously through a non-hydrolytic sol-gel process. The new HYBRIMER shows efficient index control and minor volume contraction behavior during micro-scale molding. In hybrid materials, the methacrylic end-group is considered suitable for cross-linking during the UV curing step, while the fluorinated functionality is appropriate for refractive index control. As the fluorinated silane contents are varied, the structural evolution and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…In fact, pillar collapse was observed in pillars with aspect ratios > 5, in accordance with theoretical predictions. [31][32][33][34][35][36][37][38] Higher aspect ratios can be obtained by molding with harder materials, e.g., composite PDMS, [36,37,39] bilayer PDMS, [34,37,40] photocurable PDMS, [39,41] polyolefins, [42] PDMS with polymer-reinforced sidewalls, [43] fluoropolymers, [44][45][46] photocurable perfluoropolyethers, [47] photocurable fluorinated organic-inorganic hybrids [44,[48][49][50][51][52] or photocurable polyurethane acrylates. [53,54] Molding was also performed with elastomeric silicones used in the dental clinic for making denture impressions: Provil Novo, President and P2 (see Experimental part for details).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, pillar collapse was observed in pillars with aspect ratios > 5, in accordance with theoretical predictions. [31][32][33][34][35][36][37][38] Higher aspect ratios can be obtained by molding with harder materials, e.g., composite PDMS, [36,37,39] bilayer PDMS, [34,37,40] photocurable PDMS, [39,41] polyolefins, [42] PDMS with polymer-reinforced sidewalls, [43] fluoropolymers, [44][45][46] photocurable perfluoropolyethers, [47] photocurable fluorinated organic-inorganic hybrids [44,[48][49][50][51][52] or photocurable polyurethane acrylates. [53,54] Molding was also performed with elastomeric silicones used in the dental clinic for making denture impressions: Provil Novo, President and P2 (see Experimental part for details).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, residual silanol groups may be present. Especially for prepolymers with organic group content, there might be a relatively smaller number of residual uncondensed silanol groups because of sterical hindrance around the organic group site [18]. The reduced [OH]/ [M] ratio indicated that the end-cap was nearly complete.…”
Section: Chemical Structure Analysis Of Silicone Resinmentioning
confidence: 99%
“…38,96 It has been tried out as imprint resist, 99 but since the viscosity of the fluorinated prepolymer was rather high, it left a rather thick residual layer. The material is more interesting to be applied in nanopatterned moulds for imprinting other materials.…”
Section: Glasses and Hybrids For Optics And Dielectricsmentioning
confidence: 99%